2013
DOI: 10.1111/1745-7599.12023
|View full text |Cite
|
Sign up to set email alerts
|

Gaps in the primary care of rural and underserved populations: The impact of nurse practitioners in four Mississippi Delta states

Abstract: More APNs, especially nurse practitioners (NPs), are needed to address the PCP shortage. But more than just increased numbers of NPs is the need for redistribution of these providers. Efforts to expand the scope of practice and limit regulatory restrictions will enable NPs to practice more autonomously, which in turn will provide opportunities for better access and improved healthcare outcomes, especially in rural and underserved regions. Educational programs must include competencies and skill sets focused on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 11 publications
(16 reference statements)
1
12
0
Order By: Relevance
“…NPs' workplace addresses indicated 60% of them were employed in rural settings and 35% were employed in HPSAs. A decade later, Odell, Kippenbrock, Buron, and Narcisse (2013) found similar results with white female and MSN-prepared NPs. Fifty-four percent practiced in a rural area and 24% practiced in a designated HPSA.…”
Section: Previous Np Workforce Research In the Southern United Statessupporting
confidence: 57%
“…NPs' workplace addresses indicated 60% of them were employed in rural settings and 35% were employed in HPSAs. A decade later, Odell, Kippenbrock, Buron, and Narcisse (2013) found similar results with white female and MSN-prepared NPs. Fifty-four percent practiced in a rural area and 24% practiced in a designated HPSA.…”
Section: Previous Np Workforce Research In the Southern United Statessupporting
confidence: 57%
“…Another finding of this study was that the proportion of individuals with at least 1 preventive dental checkup in a year, based on region, was the lowest in the South. Southern states, compared to the rest of the country, have a lower density of health staff and physicians, which includes oral health care providers, to provide care to the population . At the state level, in 1 study, researchers surveyed and screened patients of a rural Oregon family medicine practice.…”
Section: Discussionmentioning
confidence: 94%
“…Southern states, compared to the rest of the country, have a lower density of health staff and physicians, which includes oral health care providers, to provide care to the population. 37 At the state level, in 1 study, researchers surveyed and screened patients of a rural Oregon family medicine practice. They found that 28% of the patients reported experiencing unmet dental needs, and half of the patients who were screened had oral health conditions detected.…”
Section: Discussionmentioning
confidence: 99%
“…Their healthcare services are considered to be a substitution for primary care physicians with a positive effect on patient satisfaction and lower mortality (Kippenbrock et al., ; Martinez‐Gonzalez et al., ). Thus, it is important not only to educate NPs for primary care but also to recruit and retain NPs to improve access to care for rural residents, and because job satisfaction is important for the recruitment of healthcare professionals (Odell, Kippenbrock, Buron, & Narcisse, ; Pron, ), the nature of job satisfaction among rural NPs should be examined further.…”
Section: Discussionmentioning
confidence: 99%